Peran Efisiensi Operasional Dan Risiko Kredit Dalam Meningkatkan Kinerja Keuangan Bank Perkreditan Rakyat - Indraswari, I Gusti Agung Ayu Pramita; Dewi, Putu Pande R. Aprilyani; Budiadnyani, Ni Putu (Politeknik Negeri Ambon, 2024)
This study aims to analyze the effect of operational efficiency and credit risk on the financial performance of Rural Banks (BPRs) in Tabanan Regency. Operational efficiency is measured through the ratio of operating costs to operating income, while credit risk is calculated using the ratio of non-performing loans. Financial performance was assessed based on Return on Assets (ROA). The research was conducted on 17 BPRs with a total population of 136 data obtained from quarterly reports for the 2020-2021 period. The results of the analysis show that operational efficiency has an influence on financial performance, while credit risk has no effect on financial performance. This finding supports agency theory, which explains that managing operational efficiency can minimize conflicts of interest between managers and owners thereby improving financial performance. Conversely, the insignificant effect of credit risk indicates the need for more effective risk management strategies. This research is expected to contribute to the development of managerial strategies and policies at BPRs to improve their financial performance. Keyword: operational efficiency, credit risk, financial performance Â